Stensalmer – selvforhold og parallelisme i Salmernes Bog belyst ud fra Günter Bader og Paul Ricoeur - Pallesen, Carsten (Dansk Teologisk Tidsskrift, 2012)
The article, “Petrifi ed Psalms: Self-relation and parallelism in the Book of Psalms in the light of Günter Bader and Paul Ricoeur”, presents two systematic readings of the Book of Psalms: Günter Bader’s Psalterspiel 2009 addresses the Book of Psalms as a whole, while Paul Ricoeur offers an interpretation of Psalm 22 in the context of his intertexual reading of the Passion in St.Mark and within the symbolic network of the Biblical texts. In each of the two different approaches, the article adresses the question about divine self-relevation: the Name of God, in Ex 3:14 (“I am who I am”) and human self-relation as it is accentuated in a biblical formula of self-presentation: “I am poor” (ani/ aani). The article addresses the putative impact of biblical parallelism and self-presentation on modern philosophy of subjectivity in Herder and German idealism, classical strucuralism in Roman Jakobson and post-structuralism in Jacques Derrida and Gilles Deleuze. Leaning on Winfried Menningshaus and Bader it is argued that the Psalms have a role of a vanishing or repressed mediator for philosophy of subjectivity. This function is captured by the romantic metaphor ‘petrifi ed psalms’.